Association of Lipid Profile, Glycosylated Haemoglobin (HbA1C) and Body Mass Index (BMI) in Patients with Type- 2 Diabetes Mellitus. - Muhammad Rehan , Muhammad Shais Khan , Saman Waqar , Haroon Khan (Journal of Rawalpindi Medical College, 2018)
Methods: In this cross sectional study two hundred-thirty six diabetic patients (126 males and 110 females) participated. Patients included in the study were newly diagnosed as diabetic according to WHO criteria. Dyslipidemia was defined by presence of one or more than one abnormal serum lipid concentration, according to National Cholestrol Education Program Adult Treatment Panel III (NCEP ATP III) guideline. Weight was measured using electronic digital scales. Height was measured using a wall-mounted stadiometer. BMI was subsequently calculated as weight (kg) per height (m2). Fasting plasma glucose and 2h-BG (after 75 g glucose load) were estimated for all studied subjects. Three ml of blood was collected in EDTA bottles for measurement of HBA1c by immunoturbimetry method. Statistical analysis was performed using t-test. Significance was defined as p˂0.05. Results: Of the 236 patients, 126 patients were male and 110 were female ranging from the age group 35-80 years. The mean BMI 24.3, Total Cholesterol 163.9 mg/dl, TGL 126.8mg/dl, HDL 29.9 mg/dl, VLDL 31.6 mg/dl, LDL 108.7 mg/dl was seen in patients having HbA1c of less than 6.5. The mean HbA1c 6.7%, Total Cholesterol 160.3 mg/dl, TGL 146, HDL 27.3 mg/dl, VLDL 37.6 mg/dl, LDL 101 mg/dl was seen in patients having BMI of less than 25. Conclusion: There is a direct association of high BMI, elevated HbA1c and deranged lipid profiles in patients of diabetes mellitus. HbA1c and BMI showed positive correlation with lipid profile including total Cholesterol, LDL, TGL, VLDL & negative correlation was found with HDL levels.